2005
DOI: 10.1080/00016350500264313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of framework configuration on the marginal adaptation of zirconium dioxide ceramic anterior four-unit frameworks

Abstract: Within the limitations of this study, the framework configuration influences the marginal adaptation of anterior four-unit FPD frameworks that are manufactured from partially sintered ZrO2 ceramics independently of CAD/CAM system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 19 publications
2
52
0
2
Order By: Relevance
“…It has been previously shown that green and pre-sintered four-unit zirconia ceramic FPD frameworks of straight design exhibited better marginal adaptation compared to curved design. 13 These results were attributed largely to the distortion of the framework due to shrinkage of the ceramics during the final sintering stage. However, in that study, the marginal discrepancies of the four-unit FPD frameworks had been measured with no veneering ceramic.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been previously shown that green and pre-sintered four-unit zirconia ceramic FPD frameworks of straight design exhibited better marginal adaptation compared to curved design. 13 These results were attributed largely to the distortion of the framework due to shrinkage of the ceramics during the final sintering stage. However, in that study, the marginal discrepancies of the four-unit FPD frameworks had been measured with no veneering ceramic.…”
Section: Discussionmentioning
confidence: 98%
“…30 Although detailed cross-sections were obtained, also allowing for internal fit measurements of the crowns, it was not assessed in the current study, since the aim was to offer an appropriate finish line design against debate on the marginal fit of the zirconia crowns. 13 It was reported that there were no significant differences between the shoulder and chamfer preparation types 27 and among the mesial, distal, buccal and lingual aspects in a study conducted on Cerec3 crowns. In that study, each crown margin was evaluated in 360°, and another study revealed non-significant differences in marginal fit between metal-ceramic and all-ceramic crowns, where the margins were evaluated in 360°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marginal adaptation is essential in increasing the long-term success of a restoration 11) . Optimal marginal adaptation is an important factor in the biologic and mechanical stabilization of the fixed prosthesis.…”
Section: Discussionmentioning
confidence: 99%